"Caracterización microbianas y fermentativas del ensilaje de híbridos de maíz (Zea mays) bajo dos edades de corte y sesenta días de fermentación - Mora Espinoza, Fausto Javier (2015)
The research aímed to determine the microbial and fermentative characterístics of the silage corn hybridos under two cutting ages sixty days of fermentation. An experimental design was used vompletely randomized with a bi-factorial arrangement of two ages 60 and 75 days por four ............................................................................